Noosphere pedagogical paradigm as the conceptual basis of fundamentalization of the physical training and health-improving education of students - Zavydivska N.N (Kharkov National Pedagogical University, 2012)
It is grounded noosphere pedagogical paradigm as conceptual basis of fundamentalization athletic-health-improvement educations of students. Noosphere essence of physical education and health-preserving teaching of students is exposed. It is integrated basic aspects of maintenance of noosphere of pedagogical paradigm of fundamentalization athletic-health-improvement educations. The necessity of education of integral, healthy thought of man is marked, providing with his effective instruments for the independent conduct of healthy way of life. Abilities to put aims, to choose facilities of physical culture and to see the consequences of the actions in a state of the health are separately selected.